METODOLOGI TAFSIR AL-KHAZIN (LUBAB AL-TA’WIL FI MA’ANI AL-TANZIL) - Marlinda, Marlinda; Hasan, Hasmulyadi; Juswandi, Juswandi (TAFASIR: Journal of Quranic Studies, 2025)
Lubab al-Ta’wil fī Ma‘ani al-Tanzil by ‘Ala’ al-Din ‘Ali ibn Muhammad al-Khazin (d. 741 AH) is a significant classical tafsir work in Islamic scholarship. Compiled in the 8th century H, this work serves as a summarized version of al-Baghawi’s Ma‘alim al-Tanzil and al-Nasafi’s Madarik al-Tanzil, aiming to streamline complex commentaries while retaining their essential messages. This study explores the methodological framework employed by al-Khazin in interpreting the Qur’an, using a qualitative library research approach with content analysis as the primary method. The findings reveal that al-Khazin adopted the analytical (tahlili) method with a dominant reliance on transmitted reports (bi al-ma’tsur), though he also utilized rational interpretation (bi al-ra’y) where appropriate. His exegetical style reflects strong historical, legal, and spiritual dimensions. The distinctiveness of his tafsir lies in his meticulous hadith sourcing, critical stance toward unreliable isra’iliyyat, detailed elaboration on juridical issues, and integration of Sufi insights rooted in prophetic traditions. This research underscores the importance of a methodological reading of classical tafsir to bridge the gap between textual interpretation and contemporary contextual understanding.Keywords: Tafsir al-Khazin, tafsir methodology, classical exegesis, bi al-ma’tsur, historical approach.